HIERARCHY AND RESPECT FOR ELDERS: REFLECTION OF FAMILY VALUES IN THE PAREMIOLOGICAL FUND OF THE RUSSIAN AND UZBEK LANGUAGES - Davlatmuratov Siroj Ravshanbekovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. The article presents a comparative linguocultural analysis of the representation of the concepts of "hierarchy" and "respect for elders" in the paremiological fund of the Russian and Uzbek languages. Based on proverbs and sayings, the universal features and ethnocultural specificity of the verbalization of family values are examined. A corpus of 150 paremiological units (75 Russian and 75 Uzbek) was selected using continuous sampling. It has been established that the sacred- institutional character of hierarchy (based on the category of duty — farz) dominates in the Uzbek linguistic picture of the world, while in Russian paremiology the authority of elders is based primarily on empirical life experience and pragmatic irony. The results contribute to a deeper understanding of the mechanisms of intercultural communication and the preservation of the national code.